High-Throughput Kinetic Screening of Hybridomas to Identify High-Affinity Antibodies Using Bio-Layer Interferometry. (April 2015) - Lad, Latesh; Clancy, Sheila; Kovalenko, Maria; Liu, Chian; Hui, Terence; Smith, Victoria; Pagratis, Nikos
Kinetic analysis of antibodies is crucial in both clone selection and characterization. Historically, antibodies in supernatants from hybridomas are selected based on a solid-phase enzyme-linked immunosorbent assay (ELISA) in which the antigen is immobilized on the assay plate. ELISA selects clones based on a combination of antibody concentration in the supernatant and affinity. The antibody concentration in the supernatant can vary significantly and is typically unknown. Using the ELISA method, clones that express high levels of a low-affinity antibody can give an equivalent signal as clones that express low levels of a high-affinity antibody. As a consequence, using the ELISA method, superior clones can be overshadowed by inferior clones. In this study, we have applied Bio-Layer Interferometry to screen hybridoma clones based on disassociation rates using the OctetRED 384 platform. Using the OctetRED platform, we were able to screen 2000 clones within 24 hours and select clones containing high-affinity antibodies for further expansion and subsequent characterization. Using this method, we were able to identify several clones producing high-affinity antibodies that were missed by ELISA.